2018
DOI: 10.1007/s11571-018-9511-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on sad emotion regulation in young women: an electroencephalograph study

Abstract: The effects of exercise on cognitive abilities have been studied. However, evidence regarding the neural substrates of sad emotion regulation is limited. Women have higher rates for affective disorders than men, but insufficient outcomes assess how aerobic exercises modulate central frontal activation in sad emotion inhibition and resilience among healthy women. This study investigated the effects of aerobic exercise-related brain activity on sad emotion inhibition processing in young women. Sad facial Go/No-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 76 publications
0
12
0
1
Order By: Relevance
“…Keyword combinations and MeSH terms employed in the search are listed in Table 1 . Ten additional references were retrieved from the reference lists of the following papers in addition to the database search: Eslinger and Tranel ( 2005 ), Nishiguchi et al ( 2015 ), Park et al ( 2015 ), Di Fronso et al ( 2016 ), Fargier et al ( 2017 ), Gourgouvelis et al ( 2017 ), Yamashiro et al ( 2018 ), Hwang et al ( 2019 ), Nakata ( 2020 ), and Parr et al ( 2020 ). As for the additional references, Wei and Li ( 2017 ) and Wei and Li ( 2018 ), which were written in Chinese, were found within full-text articles being screened for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Keyword combinations and MeSH terms employed in the search are listed in Table 1 . Ten additional references were retrieved from the reference lists of the following papers in addition to the database search: Eslinger and Tranel ( 2005 ), Nishiguchi et al ( 2015 ), Park et al ( 2015 ), Di Fronso et al ( 2016 ), Fargier et al ( 2017 ), Gourgouvelis et al ( 2017 ), Yamashiro et al ( 2018 ), Hwang et al ( 2019 ), Nakata ( 2020 ), and Parr et al ( 2020 ). As for the additional references, Wei and Li ( 2017 ) and Wei and Li ( 2018 ), which were written in Chinese, were found within full-text articles being screened for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of different intensities and rest period during resistance exercise on anxiety and negative affect were examined (Bibeau et al, 2010 ). The benefits of aerobic exercise on the neural efficiency in responding to sad emotion-eliciting cues were found (Hwang et al, 2019 ). Frequent PE may improve the efficiency of controlling negative emotions in women (Ligeza et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Distinguishing stimulus and cognitive processes are closely related to attention during the tasks [ 42 ]. Hwang et al found reduced N2 activation in the central lobe and occipital cortex after acute aerobic exercise [ 43 ]. Similarly, a decreased N2 amplitude and longer N2 latency were observed during exercise [ 44 ].…”
Section: Discussionmentioning
confidence: 99%